Structural characteristics of corrugated sandwich rectangular pressure vessels - Lingxue Zhu; Yuan Fang; Yifan Shen; Hongfeng Li; Yitong Wang; Xiaolei Zhu; Xiaofeng Lu (Scientific Reports)
Abstract Rectangular cross-section pressure vessels are favored for point-to-point liquid cargo transportation due to their compact structure, stability, and high volumetric efficiency. However, they suffer from insufficient local stiffness, resulting in lower load-bearing capacity compared to circular cross-section pressure vessels. The corrugated sandwich structure offers excellent bending performance, lightweight properties, and ease of forming. This paper proposes and designs a rectangular pressure vessel enhanced with a corrugated sandwich structure. Finite element analysis is employed to study its load-bearing characteristics, and the mechanical model is simplified accordingly. A deviation of 4.55% was found through theoretical calculations, confirming the accuracy of the finite element analysis results. The new pressure vessel design increases volume by 17.2% compared to traditional designs. The ratio of the moment of inertia of the circumferential reinforcement structure ( $$I_{z\;sq}$$ ) to that of the external corrugated sandwich structure ( $$I_{z\;sd}$$ ), denoted as Π 1. As the parameter Π 1 increases, the average displacement and maximum stress show an increasing trend, stabilizing when Π 1 ≥ 1.14. With the increase of Π 2, the average displacement rises, while the maximum stress first increases and then decreases, reaching its minimum at Π 2 = 1.55.